6"'-O-acetylisospinosin, a new C-glycosylflavone and known compounds from the aerial parts of Cladanthus mixtus. Issue 20 (17th October 2020) - Benmerache, Abbes; Alabdul Magid, Abdulmagid; Kabouche, Ahmed; Harakat, Dominique; Voutquenne-Nazabadioko, Laurence; Kabouche, Zahia
Abstract: A new C -glycosylflavone, identified as 6"'- O -acetylisospinosin (1), was isolated from the aerial parts of Cladanthus mixtus together with 30 known compounds. The structures of these compounds were established by interpretation of their spectral data, mainly UV, 1D and 2D NMR spectroscopic methods including ( 1 H and 13 C NMR, COSY, ROESY, HSQC and HMBC experiments), ESI-MS, and by comparison with the literature data. Graphical Abstract: